MAS-SHAAD: a multiagent system proposal for an adaptive hypermedia system. (29th November 2004) - Merida, David; Fabregat, Ramon; Arteaga, Carlos; Cannataro, Mario
The concept of m-learning covers a wide range of possibilities opened up by the convergence of new mobile technologies, wireless infrastructure and e-learning developments. This actual convergence has launched new goals to support this mobile educational system, where the heterogeneity problem (in terms of access devices, bandwidth of the network, preferences/characteristics of the user, etc.) has become one of the major problems to be solved in this kind of mobile learning environment. Different alternatives have been developed in order to allow access to any type of content from anytime-anywhere-anyhow, and the adaptive hypermedia systems (AHS) have emerged as a solution for this. At the same time, a growing interest in multiagent systems (MAS), which have become one of the most powerful software engineering approaches to develop applications in multiple and complex domains, has emerged. In previous works, we considered the hypermedia adaptation along different "adaptivity dimensions", that take into account the heterogeneity problem. According to this, we present a design proposal of an MAS for an AHS applying the well-known GAIA methodology. Furthermore, in order to complement the conceptual definition, we graphically represent the proposed MAS-SHAAD using Agent UML (AUML) notation.